KEMANDIRIAN BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR SELAMA PEMBELAJARAN JARAK JAUH - Bagus Putra Sanjaya; Wawan Setiawardani (PGSD UNIKA SANTU PAULUS RUTENG, 2022)
The outbreak of the Covid-19 pandemic has forced the government in the education sector to implement a distance learning policy. However, this policy is not easy to implement at the basic education level. Therefore, this study aims to determine the implementation of distance learning in students of class V UPTD SDN 2 Karangampel Kidul and the learning independence that is formed in students during distance learning. This study uses a phenomenological study design with participatory observation data collection techniques, in-depth interviews that are unstructured and open, and documentation. Participants in the study were students and teachers of class V UPTD SDN 2 Karangampel Kidul obtained through purposive sampling technique. The results showed that distance learning at UPTD SDN 2 Karangampel Kidul at the beginning of the pandemic was considered not optimal because of the limited use of learning media and the implementation of learning that was still oriented to assigning tasks. However, in the new school year, educators collaborate with each other in compiling materials by varying various applications and platforms, and taking advantage of the assignment book submission schedule to repeat difficult material, so that learning activities run optimally. The learning independence of students during distance learning is considered to have developed, which is indicated by 1) most of the students communicate with friends and educators either through social media or directly with confidence; 2) most of the students do the assignments at the beginning of the time after the teacher sends the assignments and uses their cellphones to study; 3) all students have the initiative when facing difficulties during distance learning such as taking lessons, asking family members, learning little by little when lazy, and doing their favorite activities after finishing studying; and 4) most of the students have aspirations and preferences for certain subjects, so that they excel and enjoy the distance learning process.